A personal construct approach to employability: comparing stakeholders' implicit theories. Issue 4 (5th April 2019) - Williams, Stella; Karypidou, Anatoli; Steele, Catherine; Dodd, Lorna
Abstract : Purpose: The purpose of this paper is to adopt the perspective of personal construct theory to conceptualise employability. The study explores differences in the implicit employability theories of those involved in developing employability (educators) and those selecting and recruiting higher education (HE) students and graduates (employers). Design/methodology/approach: A repertory grid technique (RGT) was employed to uncover the implicit theories of 22 employers and 14 educators across the UK. Findings: A total of 717 constructs were elicited. A differential analysis of data gathered demonstrated several areas of consensus among employers and educators (including emotional management, confidence, professionalism), as well as divergence in representations of commitment, proactivity, interpersonal competencies and vision to the conceptualisation of employability. Practical implications: Findings from this analysis indicate a need to integrate group process assessments within undergraduate programmes and recruitment procedures. Originality/value: This study represents a personal construct approach to employability, utilising the unique value of RGT to further inform our understanding of employability within an HE context. This study contributes to an understanding of employability as a continually re-constructed concept. This study provides insights to its nature via two information rich cases that have extensive knowledge on the topic.